Penentuan Resiko Dan Kerentanan Tsunami Di Kebumen Dengan Citra Alos - Faiz Islam; Sawitri Subiyanto; L. M. Sabri (Departement Teknik Geodesi Universitas Diponegoro, 2014)
Indonesia is the country that has the potential for major natural disasters due to a ring of fire around . One of the risk is tsunami . Kebumen is a district in Central Java has the potential to be exposed to the risk of a tsunami . Kebumen geographically located at 7 ° 27 ' - 7 ° 50 ' south latitude and 109 ° 22 ' - 109 ° 50 ' which has 35 km along the southern coast . Prevention needs to be a systematic way of determining the risks and vulnerabilities to prevent the disaster victims .The method used in this study is the determination of risk is the Run - Up Regulation of the Minister of Public Works No.06/PRT/M/2009 . In addition to satellite imagery used is the image of ALOS ( Advanced Land Observing Satellite ) is from Japan . Vulnerability parameters to be obtained in the form Slope , population density , distance from the coast .Vulnerability of the parameters obtained will be weighted by Pairwise Comparison method . After that it will be overlay by risk . Then formed Vulnerability and Risk maps Kebumen tsunami . Then formed Vulnerability and Risk Tsunami in Kebumen . From result that area in kebumen have impact with tsunami for elevation run-up 0-16 m is 44,16%, then area save from tsunami is 56,484%. Mirit, Ambal, Buluspesantren, Kuwarasan and Ayah is districk with more risk than any other area.Keywords : Kebumen, , Run-Up, Tsunami, Vulnerability, risks